2010
DOI: 10.1007/s00442-010-1828-5
|View full text |Cite
|
Sign up to set email alerts
|

Foraging patterns of acorn woodpeckers (Melanerpes formicivorus) on valley oak (Quercus lobata Née) in two California oak savanna-woodlands

Abstract: Landscape characteristics and social behavior can affect the foraging patterns of seed-dependent animals. We examine the movement of acorns from valley oak (Quercus lobata) trees to granaries maintained by acorn woodpeckers (Melanerpes formicivorus) in two California oak savanna-woodlands differing in the distribution of Q. lobata within each site. In 2004, we sampled Q. lobata acorns from 16 granaries at Sedgwick Reserve in Santa Barbara County and 18 granaries at Hastings Reserve in Monterey County. Sedgwick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…Although woodpeckers are more likely to acts as seed consumers than dispersers, they transport acorns to 'granaries', which are storage sites often in the barks of trees, and can be considered to be seed pools (Grivet et al 2005). Woodpeckers can fly kilometers on any given day, but our analyses showed that the effective number of maternal trees found in any single granary (each containing the combined collection from a single woodpecker family's efforts) is 2-3 local trees (Scofield et al 2010;Scofield et al 2011), as would be predicted by optimal foraging theory (Thompson et al 2014).…”
Section: Seed Movement At a Landscape Scalementioning
confidence: 82%
“…Although woodpeckers are more likely to acts as seed consumers than dispersers, they transport acorns to 'granaries', which are storage sites often in the barks of trees, and can be considered to be seed pools (Grivet et al 2005). Woodpeckers can fly kilometers on any given day, but our analyses showed that the effective number of maternal trees found in any single granary (each containing the combined collection from a single woodpecker family's efforts) is 2-3 local trees (Scofield et al 2010;Scofield et al 2011), as would be predicted by optimal foraging theory (Thompson et al 2014).…”
Section: Seed Movement At a Landscape Scalementioning
confidence: 82%
“…Direct observational studies of dispersal are likely to miss rare but important longer-distance dispersal events, and can pose significant challenges for tracking movement of individual seeds (Koenig et al, 1996;Nathan, 2006;Scofield et al, 2011). Currently, molecular and observational estimates of seed dispersal are rarely combined in a single study system, despite the fact that both approaches have potentially significant limitations when employed in isolation.…”
Section: Overview and Predictionsmentioning
confidence: 99%
“…Unlike umbrellabirds, acorn woodpeckers live in highly territorial social groups and tend to forage in the trees proximal to their storage sites, with each territorial group gathering acorns from non-overlapping territories and hence from different trees (Grivet et al, 2005;Scofield et al, 2010Scofield et al, , 2011). However, because lek-breeding among frugivorous bird species is essentially absent from the temperate zone, we must limit our comparisons to species that exhibit other mating systems.…”
Section: Comparisons With Other Lekking and Non-lekking Speciesmentioning
confidence: 99%
“…Extensive studies about its diet (Stacey 1981, Rosas et al 2008), parental care (Koenig & Walters 2011), population ecology (Koenig & Mumme 1987) and use of habitat (Stacey 1979, Ligon & Stacey 1996) have been done in North and Central America. A well known aspect is their strong relationship with different oak species of the genus Quercus and Notholithocarpus; from which they rely on as a food source (Scofield et al 2011) and as nest cavity sites (Koenig & Walters 2014), allowing them to survive during the winter season (Koenig & Haydock 1999). A behavior associated with the use of oaks is the accumulation of acorns or seeds in small holes in the bark of these trees (MacRoberts & MacRoberts 1976).…”
Section: Introductionmentioning
confidence: 99%